KINERJA BADAN PENDAPATAN DAERAH KOTA BEKASI DALAM PEMUNGUTAN PAJAK REKLAME: Array - Muhammad Ilham Firdaus; Rachmat Ramdani; Gili Argenti (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
The research is motivated by the problem of obtaining advertisement tax revenue in Bekasi City from 2015 to 2018 which did not reach the predetermined targets, referring to the above problems, this research aims as follows: (1) To identify and analyze the performance of employees of the Bekasi City Regional Revenue Agency ( 2) Knowing and analyzing the role of leaders (3) To identify and analyze inter-agency coordination (4) To know and analyze work systems, regulations, and facilities (5) To identify and analyze external and internal pressures in the Regional Revenue Board of Bekasi City. In this research, the research method that the researcher uses is descriptive with a qualitative approach with data collection techniques including: observation, interviews, documentation, and audio visual as well as the sampling technique used by researchers is purposive sampling. The results show that, the performance of the Bekasi City Regional Revenue Agency in collecting advertisement tax has not been optimal. For a long time, the system factor of Bekasi Mayor Regulation Number 48 of 2012 concerning Implementation Guidelines for Bekasi City Regional Regulation Number 14 of 2012 concerning Advertising Tax is no longer relevant to be applied.